2015
DOI: 10.3846/16111699.2014.964304
|View full text |Cite
|
Sign up to set email alerts
|

Is an Intertemporal Model of the Current Account Valid for East Asian Countries? Evidence From Structural Var

Abstract: This paper aims to examine the validity of present-value model of current account (PVMCA) by analyzing dynamic responses of variables in PVMCA to structural shocks. In place of the cross-equation restriction tests used in existing research, we adopted a structural vector autoregression framework and obtain three findings. First, evidences from 4 East Asian countries supported the intertemporal theoretical expectation that country-specific transitory shocks significantly affect current accounts, whereas the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…In other words, transitory specific shocks are the dominant factor in the current account fluctuations of the WAEMU economies. This result confirms the fundamental assumption of the inter-temporal approach and corresponds to that found by other studies in particular, Gregory and Head (1999) for the G7 economies, Kano (2003) in the framework of Canada and the United Kingdom and Kuo (2015) with regard to East Asian countries.…”
Section: Impulse Responses Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…In other words, transitory specific shocks are the dominant factor in the current account fluctuations of the WAEMU economies. This result confirms the fundamental assumption of the inter-temporal approach and corresponds to that found by other studies in particular, Gregory and Head (1999) for the G7 economies, Kano (2003) in the framework of Canada and the United Kingdom and Kuo (2015) with regard to East Asian countries.…”
Section: Impulse Responses Analysissupporting
confidence: 91%
“…This result is consistent with the theoretical predictions of the inter-temporal approach, which states the absence of a current account response to the global shock in a small open economy. This has also been empirically established by recent studies such as Gross (2001) and especially Kuo (2015) in the context of East Asian economies.…”
Section: Impulse Responses Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…One technique to analyze the PVM predictions is building a SVAR specification using Blanchard and Quah (1989)'s identification (BQ) to identify the persistence of the structural shocks. Under this setup, some literature include Kano (2008), Kuo (2015), Ibhagui (2017), Diallo (2020), and Bussiere et al (2021). Kano (2008) employed the basic model with uncertainty to analyze Canada and the UK.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using a four-SVAR specification to address the consumption-tilting motive via the inclusion of the real exchange rate in the analysis, 3 Kuo (2015) found that temporary shocks play a major role in the current account and net output growth fluctuations. This implies that Kano's second puzzle does not hold for Hong Kong, India, Singapore, and Taiwan.…”
Section: Introductionmentioning
confidence: 99%